Juridical Review of the Effectiveness of Implementing Internships for Extraordinary Members to Produce Professional Notaries - Oktavianto, Heri; Hafidz, Jawade (TABELLIUS: Journal of Law, 2023)
Carrying out internships for Notaries is very important, this is to improve the skills of notary candidates, however in reality the awareness of Notary candidates has not been carried out effectively, this is due to the practicism of Notary candidates who want to start practicing freshly so it is not uncommon for internships to be carried out not on time determined by existing regulations. The method in this writing is analytical descriptive. Based on the study carried out, it can be understood that the effectiveness of implementing internships for Extraordinary Members in producing professional notaries in Semarang City is currently not being able to be realized well, this is shown by the majority of Extraordinary Members who have a statement letter that they have done an internship but in reality have not done so. The internship position for Extraordinary Members to become Notaries based on Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notaries is very important, this is in accordance with Article 2 of the Indonesian Notary Association Regulation Number: 24/Perkum/Ini/ 2021 About Internships. Keywords: Effectiveness; Internship; Juridical; Notary.